"SACCIA Safe Communication": Five core competencies for safe and high-quality care. Issue 3 (June 2018) - Hannawa, Annegret F
Background: Communication has emerged as a critical component in delivering safe, high-quality care. The evidence is clear that health outcomes are enhanced when clinicians communicate well, and compromised when they interact poorly. It is important to understand the core aspects of interpersonal sense-making that hinder or foster favorable health outcomes. This study introduces an evidence-based "SACCIA Safe Communication" (S ufficiency, A ccuracy, C larity, C ontextualization, I nterpersonalA daptation) framework to fill this gap. Method: Sixty narratives of patient safety events were coded using qualitative content analysis guided by the "Hannawa SACCIA Safe Communication" framework. Results: The analyses yielded 367 communication errors. Of these errors, 160 related to unsafe encoding, 92 to unsafe decoding, and 115 to unsafe transactional communication. Sufficiency errors were most frequent (124), followed by communication errors of contextualization (117), accuracy (84), interpersonal adaptation (26), and clarity (16). Conclusions: The Hannawa SACCIA Safe Communication framework identifies interpersonal communication processes that commonly compromise the safety and quality of care. Narrative excerpts from the cases in this study exemplify what these processes look like in daily care encounters. The framework bridges across contexts and interpersonal settings. Furthermore, it explains various types of patient safety events (e.g. patient falls; unsafe handoffs or surgeries; diagnostic and medication errors). Therefore, it serves as a useful approach to describe and understand interpersonal communication as a critical factor in the provision of safe and high-quality care.